The effectiveness of group and home‐based exercise on psychological status in people with ankylosing spondylitis: A systematic review and meta‐analysis. (18th April 2022) - Lane, Brian; McCullagh, Ruth; Cardoso, Jefferson R.; McVeigh, Joseph G.
Abstract: Introduction: Ankylosing spondylitis (AS) is an inflammatory rheumatic disease in which the physical impact has been evaluated; however, the psychological consequences are less well explored. The primary aim of this review was to determine the effectiveness of group versus home‐based exercises on psychological status of patients with AS. Methods: Six databases were searched until January 2020. Eligible studies were randomised controlled trials including group or home‐based exercise interventions. Risk of bias (RoB) was evaluated using the Cochrane RoB 2.0 tool. Relative percentage difference (RPD) between groups and effect sizes were presented as standardised mean differences (SMDs) with 95% confidence intervals (CI). Results: Five studies met the inclusion criteria ( n  = 240), outcomes of interest were depression, anxiety and mental health. Three studies were low‐risk RoB, one study was high‐risk RoB and one study there was 'some concerns' of bias. Group‐based exercise was more effective than home‐based exercise for improving depression at 6‐week (RPD 18%) and 3‐month (RPD 42%), anxiety (RPD 17%) and mental health (RPD 20%). Home‐based exercise was more effective than control interventions for improving depression (RPD 33%). A meta‐analysis demonstrated group‐based exercises compared to home exercises, improved depression (SMD: −0.54; 95% CI: [−0.89; −0.18]; p  = 0.003) and physical function (SMD: −0.49; 95% CI: [−0.84; −0.14]; p  = 0.006). Conclusion: Supervised group‐based demonstrated improvements in depression, anxiety and mental health compared to home‐based exercise. Individualised home‐based exercise is more effective than no intervention for improving depression in people with AS.